OBIS-USA: A Data-Sharing Legacy of the Census of Marine Life - George R. Sedberry; Daphne G. Fautin; Michael Feldman; Mark D. Fornwall; Philip Goldstein; Robert P. Guralnick (Oceanography, 2011)
The United States Geological Survey’s Biological Informatics Program hosts OBIS-USA, the US node of the Ocean Biogeographic Information System (OBIS). OBIS-USA gathers, coordinates, applies standard formats to, and makes widely available data on biological collections in marine waters of the United States and other areas where US investigators have collected data and, in some instances, specimens. OBIS-USA delivers its data to OBIS international, which then delivers its data to the Global Biodiversity Information Facility (GBIF) and other Web portals for marine biodiversity data. OBIS-USA currently has 145 data sets from 36 participants, representing over 6.5 million occurrence records of over 83,000 taxa from more than 888,000 locations. OBIS-USA, a legacy of the decade-long (2001–2010) international collaborative Census of Marine Life enterprise, continues to add data, including those from ongoing Census projects. Among the many challenges in creating OBIS, including OBIS-USA, were developing a community of trust and shared value among data providers, and demonstrating to providers the value of making their data accessible to others. Challenges also posed by the diversity of data sets relevant to marine biodiversity stored on thousands of computers, in a variety of formats, not all widely accessible, have been met in OBIS-USA by implementing a uniform standard and publishing platform that is easily accessible to a broad range of users.